Musyawarah Perencanaan Pembangunan Kinerja Kepala Desa Sungai Musang Tahun 2021 - djaelani, syafril (PT. Bangun Harapan Bangsa, 2022)
The increased participation of village communities in the preparation of village development plans is one of the factors that becomes a benchmark for the extent to which the village develops the values ​​of good village governance in the wheels of village governance. The involvement of rural communities in a broad sense must be encouraged both through regulations and the creation of an ideal democratizing climate in the village. Participation in the context of implementing the Village Development Planning Deliberation (Musrembang) is actually more understood as the contribution of the village community to improve the effectiveness and efficiency of development. In the implementation of the Sungai Musang Village Development Planning Deliberation, the enthusiasm of the community greatly supports the success of the village meeting. With a democratic leadership style, village deliberations can run well and orderly and produce decisions that are beneficial for village development. The implementation of village deliberations is carried out by discussing finding solutions to various problems that exist in the village to find a comprehensive solution.